The Impact of Non-Performing Loan, Loan to Deposit Ratio, and Operational Cost to Operating Income Ratio on Financial Performance - Irfan Florid, Muhamad; Purnamasari, Pupung (Journal of World Science, 2023)
Various events can pose risks to the quality of Islamic banking, both globally and bring improvements and enhancements to the quality of Pandemic Covid-19, which was identified entering Indonesia since March 2, 2020, has significantly reduced economic activities, especially with the implementation of Large-Scale Social Restrictions (PSBB) since April 10, 2020. The objective of this research is to understand and analyze the impact of non-performing loans, loan to deposit ratio, operational cost to operational income on financial performance. The method used in this research is quantitative data method with hypothesis testing, employing multiple linear regression using cross-data and time series. Data management in this research is assisted using the Statistica Program for Social Science (SPSS) Version 23. The research results show that Non-Performing Loan (NPL) has a negative impact on Return On Asset (ROA), Loan to Deposit Ratio (LDR) negatively influences Return On Asset (ROA), Operational Cost to Operational Income (BOPO) has a positive impact on Return On Asset (ROA), and simultaneously the variables Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operational Cost to Operational Income (BOPO) affect Financial Performance (ROA) in Islamic Commercial Banks from 2018 to 2021. Islamic Commercial Banks are expected to be more cautious in providing financing, as the researched data shows that the level of Non-Performing Loan (NPL) ratio significantly affects the financial performance (ROA) of Islamic banks.